Juvenile hormone acid methyltransferase: A key regulatory enzyme for insect metamorphosis - Shinoda, Tetsuro (National Academy of Sciences, 2003)
Juvenile hormone (JH) acid methyltransferase (JHAMT) is an enzyme that converts JH acids or inactive precursors of JHs to active JHs at the final step of JH biosynthesis pathway in insects. By fluorescent mRNA differential display, we have cloned a cDNA encoding JHAMT from the corpora allata (CA) of the silkworm, Bombyx mori (BmJHAMT). The BmJHAMT cDNA encodes an ORF of 278 aa with a calculated molecular mass of 32,544 Da. The predicted amino acid sequence contains a conserved S-adenosyl-l-methionine (SAM) binding motif found in the family of SAM-dependent methyltransferases. Purified N-terminal 6×His-tagged recombinant BmJHAMT protein expressed in Escherichia coli catalyzed conversion of farnesoic acid and JH acids I, II, and III to their cognate methyl esters in the presence of SAM, confirming that this cDNA encodes a functional JHAMT. Putative orthologs, DmJHAMT and AgJHAMT, were identified from the genome sequence of the fruit fly Drosophila melanogaster, and a malaria vector, Anopheles gambiae, respectively. Northern blot and quantitative RT-PCR analyses revealed that the BmJHAMT gene was expressed specifically in the CA throughout the third and fourth instar. At the beginning of the last (fifth) instar, the expression level of BmJHAMT declined rapidly and became undetectable by day 4 and remained so until pupation. Correlation of the BmJHAMT gene expression and the JH biosynthetic activity in the CA suggests that the transcriptional suppression of the BmJHAMT gene is crucial for the termination of JH biosynthesis in the CA, which is a prerequisite for the initiation of metamorphosis.